ER‐aminopeptidase 1 determines the processing and presentation of an immunotherapy‐relevant melanoma epitope. Issue 2 (27th November 2019) - Textoris‐Taube, Kathrin; Cammann, Clemens; Henklein, Petra; Topfstedt, Eylin; Ebstein, Frédéric; Henze, Sarah; Liepe, Juliane; Zhao, Fang; Schadendorf, Dirk; Dahlmann, Burkhardt; Uckert, Wolfgang; Paschen, Annette; et al.
Abstract: Dissecting the different steps of the processing and presentation of tumor‐associated antigens is a key aspect of immunotherapies enabling to tackle the immune response evasion attempts of cancer cells. The immunodominant glycoprotein gp100209‐217 epitope, which is liberated from the melanoma differentiation antigen gp100 PMEL17, is part of immunotherapy trials. By analyzing different human melanoma cell lines, we here demonstrate that a pool of N‐terminal extended peptides sharing the common minimal epitope is generated by melanoma proteasome subtypes. In vitro and in cellulo experiments indicate that ER‐resident aminopeptidase 1 (ERAP1)—but not ERAP2—defines the processing of this peptide pool thereby modulating the T‐cell recognition of melanoma cells. By combining the outcomes of our studies and others, we can sketch the complex processing and endogenous presentation pathway of the gp100209‐217 ‐containing epitope/peptides, which are produced by proteasomes and are translocated to the vesicular compartment through different pathways, where the precursor peptides that reach the endoplasmic reticulum are further processed by ERAP1. The latter step enhances the activation of epitope‐specific T lymphocytes, which might be a target to improve the efficiency of anti‐melanoma immunotherapy. Abstract : The gp100209‐217 CD8 + T cell epitope derived from melanoma antigen gp100 PMEL17 is a potential target in immunotherapy. This study demonstrates that melanoma proteasomes generate only N‐terminal extended epitope precursors, whereas the minimal gp100209‐217 epitope is exclusively generated by ER‐aminopeptidase 1 (ERAP1), suggesting strategies enhancing ERAP1 activity could improve epitope‐specific immunotherapies.